Immunohematopathology markers in paraffin sections - Bacchi, C. E.; Bacchi, M. M. (Natl Soc Histotechnology, 1999)
New monoclonal antibodies have made the use of formalin fixed, paraffin embedded sections practical for immunotyping and immunodiagnosing many hematolymphoid neoplasms. In addition, they can be helpful in classifying malignant lymphomas and leukemias through patterns of immunoreactivity. The most useful. lymphoid antibodies and diagnostic situations in which they can be deployed are discussed.